Vibrational, Ultra Violet, Natural Bond Orbital Analysis of E-1 using Quantum Mechanical Computations and Experimental Spectra. - D.Sumathi,; H., Saleem; S.Srinivasan,; N.RameshBabu,; D.Usha, (Journal of New Developments in Chemistry, 2016)
The FT-IR, FT-Raman and UV-Vis spectra of E-[1-(3'-methylthienyl)-5-Phenyl-2,4-Pentadiene-3-one (MPPO) were recorded. The optimized molecular bond parameters, harmonic frequencies were calculated using B3LYP method with 6-311++G (d,p) basis set.The various normal modes were precisely assigned with thehelp ofTED calculation. The theoretical spectrograms for FT-IR, FT-Raman and Ultra Violet visible. Spectra of the title molecule had been constructed. The ICT was calculated by means of Natural Bond Orbital analysis. The Non Linear Optical properties related to polarizability and hyperpolarizability based on the finite-field approach were calculated.The band gap energy was calculated using HOMO-LUMO analysis. Furthermore, the Molecular Electrostatic Potential, Mulliken atomic charges and thermodynamic properties of MPPO were also calculated.
Keywords: MPPO; DFT; NLO; NBO; MEP